Dietary inflammatory index and its associations with cardiovascular diseases and cancer: Evidence form NHANES 2017–2018 and Mendelian randomization analysis - Xuehua Wang; Qian Xu; Wenhu Liu; Jingjie Xiong; Han Li; Ni Xiong; Yan Wang; Zhaohui Wang (Experimental Gerontology)
Objective: Cardiovascular diseases (CVDs) and cancer are significant global causes of mortality. However, the link between diets that promote inflammation and various subtypes of CVDs and cancers remains unclear. Methods: Utilizing the dataset from the 2017–2018 National Health and Nutrition Examination Survey (NHANES) data release cycle, our study encompassed 3538 adult participants within the age range of 20 to 80 years. The dietary questionnaire information was utilized to calculate dietary inflammatory index (DII) scores. Logistic regression analysis was employed to validate the association between the DII and CVDs, as well as overall cancer and special type cancer. Mediation analysis was conducted to evaluate the relationship between DII and the aforementioned diseases, with hemoglobin serving as the potential mediator. Mendelian randomization (MR) analysis externally validated hemoglobin's causal link to these diseases. Results: Patients with the highest quartile levels of DII scores demonstrated an elevated prevalence of congestive heart failure (CHF), stroke, overall cancer and some specific types of cancers. The logistic regression analysis revealed a correlation between DII and CHF (OR = 1.197, p = 0.002), stroke (OR = 1.205, p < 0.001), as well as breast cancer (OR = 1.306, p = 0.004). The pro-inflammatory diet also resulted in lower hemoglobin levels (p < 0.001). Mediation analyses found a role for hemoglobin in the relationship of DII and CVDs. Conclusions: Both CVDs and cancer risk were positively correlated with the DII in our study. Hemoglobin emerged as a potential mediator in the intricate relationship between DII and CHF, as well as stroke.